O cartaz político e poético: revolução em imagens - Rubens Rangel Silva (2017)
The proliferation of posters in the June Journeys was a true resumption of the graphic language of protest in the public space as a weapon in the confronting dissent. We will see what the political posters tell us that colored and scrawled the streets of Brazilian cities in the midst of porreradas, shots, gasses, explosions and bombs of all kinds. What new fictions, what new worlds, what new lives, what new relations, what new cities do we propose to the street armed with cardboard and armed with colored pens? We will see how it was that the brave boys and girlsof Brazilian cities, armed with posters and vinegar, shook the power and set fire to the imagination of a country, that wished the spring in the middle of winter.